PSI-19 Effect of extended colostrum feeding on serum IgG in newborn calves. (7th December 2018) - Pletts, S; Pyo, J; He, S; Haines, D; Guan, L; Steele, M
Abstract: Colostrum is commonly fed to dairy calves for only one meal as it is thought that intestinal closure limits IgG transfer after the first day of life. The objective of this study was to determine how feeding colostrum beyond the first meal affects passive transfer of IgG. Twenty-seven Holstein bull calves were fed colostrum (62 g IgG/L; 7.5% of BW) at 2 h postnatal, randomly assigned to 1 of 3 treatments, then fed at 5% of BW at 12, 24, 36, 48, 60 h. Treatments were colostrum (COL), 1:1 colostrum:milk (MIX), or MILK. A jugular catheter was inserted at 1 h postnatal for blood collection over 75 h. Data were analyzed using the MIXED procedure of SAS, with significance declared at P ≤ 0.05. MILK had a lower ( P < 0.05) maximum IgG concentration (22.4 g/L) and reached max IgG earlier (12 vs. 21 h) compared to MIX and COL (25.0 g/L and 30.0 g/L, respectively). Minimum IgG concentration was 21.0 and 30% lower ( P < 0.05) for MILK relative to MIX and COL, respectively. The overall decrease in total IgG transfer for MILK is reflected in an area under the curve that was less ( P < 0.05) for MILK at 24 h (279.9 g/L × h) compared to MIX and COL (330.7 and 391.1 g/L × h, respectively). Although apparent efficiency of absorption (AEA) for MIX and COL decreased ( P < 0.01) following the initial colostrum meal at 2 h, there was no difference in AEA between MIX and COL at 24 h (2.3 and 0.9 g/L, respectively). These results suggest that the neonatal intestine is still permeable to IgG past 12 h, and feeding a colostrum or colostrum-milk mix after the first meal postnatal provides an opportunity to increase passive transfer of IgG in the neonatal dairy calf.